2004
DOI: 10.1111/j.1365-2044.2004.03972.x
|View full text |Cite
|
Sign up to set email alerts
|

B‐Type natriuretic peptide and the prediction of outcome in patients admitted to intensive care

Abstract: SummaryB-type natriuretic peptide is known to predict outcome in congestive cardiac failure and myocardial infarction. We aimed to determine whether measurement of B-type natriuretic peptide would predict hospital mortality in patients admitted to an intensive care unit. We conducted a prospective observational cohort study in 78 consecutive patients. Demographics, clinical details and clinical outcomes were recorded. Admission and 24 h B-type natriuretic peptide and cardiac troponin I levels were measured. B-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
39
0
3

Year Published

2007
2007
2019
2019

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(47 citation statements)
references
References 36 publications
(30 reference statements)
5
39
0
3
Order By: Relevance
“…In such an unselected ICU population, the clinical spectrum is wide and nonspecific. In other studies on the use of natriuretic peptides in intensive care, focus has been on specific groups of patients (60,63,68,93), and studies on NT-proBNP in general ICU populations preceding study I have been more limited in size (70)(71)(72)94). Although direct comparison between studies is complicated by differences in patient selection, the results of study I are in the same range as in preceding studies.…”
Section: Patient Selection and Settings (Papers I -Iv)supporting
confidence: 64%
See 2 more Smart Citations
“…In such an unselected ICU population, the clinical spectrum is wide and nonspecific. In other studies on the use of natriuretic peptides in intensive care, focus has been on specific groups of patients (60,63,68,93), and studies on NT-proBNP in general ICU populations preceding study I have been more limited in size (70)(71)(72)94). Although direct comparison between studies is complicated by differences in patient selection, the results of study I are in the same range as in preceding studies.…”
Section: Patient Selection and Settings (Papers I -Iv)supporting
confidence: 64%
“…We found that NT-proBNP levels close to the thresholds used clinically, and reported in other studies (70,71,94), could predict death in general intensive care patients. Statistically, the predictive ability of NT-proBNP was independent of age, ICU LOS and the presence of sepsis.…”
Section: On Predicting Cardiac Outcome In Icu Patients (Papers I -Iv)supporting
confidence: 57%
See 1 more Smart Citation
“…There is also a growing body of literature suggesting a prognostic role for BNP and its derivatives at the time of cardiac surgery [14,15]. In contrast, the role of BNP in predicting risk associated with critical illness is less clear [31][32][33].…”
Section: Prior Studiesmentioning
confidence: 99%
“…A prognostic impact of BNP was found by other authors 17,30 . In contrast, a recent study analyzing 78 patients who had been admitted to a general ICU (35 patients with sepsis) revealed higher BNP levels in survivors as compared to nonsurvivors, the same trend being observed when analysis was restricted to the patients with sepsis 31 . Other studies did not find any prognostic information from BNP levels in critically ill patients 32 .…”
Section: Discussionmentioning
confidence: 41%